ANALISIS TREND PENERIMAAN DAN EFEKTIVITAS PAJAK HOTEL DAN PAJAK RESTORAN DI KABUPATEN BOJONEGORO TAHUN 2016- 2020 (Studi Kasus pada Dinas Pendapatan Daerah Kabupaten Bojonegoro) - Ahmadi, Edy Anas (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2020)
This research aims to analysis receipts trend, effectiveness of hotel tax and restaurant tax at Bojonegoro Regency of 2016 to 2020. Hotel tax and restaurant tax is one of element ( PAD).The data used in this secondary. The secondary data were obtained from (PAD) Bojonegoro Regency. Collecting Method data was dekumentation and library reseach with analysis effectiveness hotel tax and restaurant tax in Bojonegoro Regency. The result showed the effectiveness of hotel tax and restaurant tax vary widley. The hignest level of effectiveness in 2019 amounted to 144 % and the lowest in 2016 amounted 80 %, overall the hotel tax effectiveness each year have increased and decreased. WhereasÂ restaurant tax in Bojonegoro Regency the hignes level of effectiveness in 2016 amonted to 408 %, the lowest in 2020 amounted 134 %. Effectiveness restaurant tax show that efektif because >100 %